Computational Modeling and Theoretical Calculations on the Interactions between Spermidine and Functional Monomer (Methacrylic Acid) in a Molecularly Imprinted Polymer - Yujie Huang; Qiujin Zhu (Journal of Chemistry)
This paper theoretically investigates interactions between a template and functional monomer required for synthesizing an efficient molecularly imprinted polymer (MIP). We employed density functional theory (DFT) to compute geometry, single-point energy, and binding energy (ΔE) of an MIP system, where spermidine (SPD) and methacrylic acid (MAA) were selected as template and functional monomer, respectively. The geometry was calculated by using B3LYP method with 6-31+(d) basis set. Furthermore, 6-311++(d, p) basis set was used to compute the single-point energy of the above geometry. The optimized geometries at different template to functional monomer molar ratios, mode of bonding between template and functional monomer, changes in charge on natural bond orbital (NBO), and binding energy were analyzed. The simulation results show that SPD and MAA form a stable complex via hydrogen bonding. At 1 : 5 SPD to MAA ratio, the binding energy is minimum, while the amount of transferred charge between the molecules is maximum; SPD and MAA form a stable complex at 1 : 5 molar ratio through six hydrogen bonds. Optimizing structure of template-functional monomer complex, through computational modeling prior synthesis, significantly contributes towards choosing a suitable pair of template-functional monomer that yields an efficient MIP with high specificity and selectivity.